Vibrational Spectroscopic Characterization and Structural Investigations of Cepharanthine, a Natural Alkaloid - Çelik, Sefa; AKYÜZ, SEVİM; Özel, Ayşen E. (Elsevier, 2022)
Cepharanthine, a natural alkaloid obtained from the Stephania cepharantha Hayata plant, that has anti-tumor, anti-inflammatory, antioxidative, antiparasitic, and antiviral properties, has been widely used for many years to treat a wide variety of diseases in Japan. However, to elucidate its mechanism of action needs further study. This study aimed to enlighten the molecular structure, and the anticancer and antiviral action mechanisms of Cepharanthine. To evaluate the molecular structure of Cepharanthine, conforma-tional analysis was performed using the DFT/B3LYP with 6-31G(d,p) basis set. The obtained most stable molecular geometry was then optimized at the DFT/B3LYP/6-311 ++ G(d,p) level of theory. The observed IR and Raman bands were compared with harmonic vibrational frequencies of the optimized structure of cepharanthine, calculated using the same level of theory, and assigned on the base of potential energy distribution (PED). The experimental UV-Vis absorption spectrum was recorded and compared with the simulated Time Dependent (TD-DFT/B3LYP/6-311 ++ G(d,p)) method. Moreover, (1) H and C-13 NMR spectra has been calculated and compared by the experimental spectra. To reveal pharmacological importance of Cepharanthine, a molecular docking study was performed with NF-kappa B (nuclear factor kappa-light-chain-enhancer of activated B cells) receptor which controls transcription of DNA, cytokine production and cell survival. Molecular docking simulations revealed that Cepharanthine showed strong binding affinity to NF-kappa B receptor ( Delta G = -8.9 kcal/mol). In addition, to enlight the antiviral properties of cepharantine and to explore the possibility of its use in the treatment of COVID-19, the interactions of cepharanthine with ACE2, apo and holo forms of COVID-19 main protease enzyme (M-pro) and spike glycoprotein of SARSCoV-2 receptors were investigated. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Cepharanthine; Density Functional Theory; FTIR; Raman